Listening to Students’ and Teachers’ Voices: Online Teaching Practices Leading to EFL Learners ' Demotivation - Erna Iftanti; Nany Soengkono Madayani; Nada Mohsen Said Ali Sherif (JEELS (Journal of English Education and Linguistics Studies), 2023)
This study was conducted in response to the online teaching practices which demotivate EFL learners in learning English from both the teachers' and students' perspectives so that it can provide an equal point of view. The study was done by distributing a questionnaire to 152 students of the State Islamic Madrasah in Tulungagung, East Java, Indonesia to find data related to those who experience demotivation in learning English and interviewing them in depth both directly and indirectly through voice notes in July to September 2022. The in-depth interview was also done to their English teachers. The result of qualitative data analysis revealed that students were demotivated, bored, and lazy during online learning because of two main factors, namely teachers, i.e., uninteresting teaching methods and techniques, lack of online teaching experience, teacher’s personality, and the usage of the online learning application. Meanwhile, the teachers perceive that their demotivating EFL teaching was resulted from students' learning loss, lack of students' learning involvement, and teachers' feeling insecure caused by some factors, namely the variety of online teaching methods, the accessibility of online learning media, family interference, and students' internal lack of motivation. Still, this demotivating online teaching and learning do not significantly implicate the students' achievement of English. These research results are pedagogically implemented to improve the quality of online teaching and learning English, mainly at the secondary levels.